Specification for textile reinforced thermoplastics hydraulic hoses and Hose Assemblies (BSI, 1984)
Flexible pipes, Thermoplastic polymers, Reinforced materials, Textile fibres, Dimensions, Designations, Design, Marking, Performance, Test equipment, Electrical testing, Electrical conductivity, Hydraulic equipment, Pressure testing